Are users of sulphonylureas at the time of an acute coronary syndrome at risk of poorer outcomes?. Issue 11 (3rd June 2013) - Nagendran, J.; Oudit, G. Y.; Bakal, J. A.; Light, P. E.; Dyck, J. R. B.; McAlister, F. A.
Abstract Aims Adenosine triphosphate sensitive potassium (KATP) channel activity is cardioprotective during ischaemia. One of the purported mechanisms for sulphonylurea adverse effects is through inhibition of these channels. The purpose of this study is to examine whether patients using KATP channel inhibitors at the time of an acute coronary syndrome are at greater risk of death or heart failure (HF) than those not exposed. Methods Using linked administrative databases we identified all adults who had an acute coronary syndrome between April 2002 and October 2006 (n = 21 023). Results Within 30 days of acute coronary syndrome, 5.3% of our cohort died and 15.6% were diagnosed with HF. Individuals with diabetes exhibited significantly higher risk of death (adjusted OR: 1.20, 95% CI: 1.03–1.40) and death or HF (aOR: 1.73, 95% CI: 1.59–1.89) than individuals without diabetes. However, there was no significantly increased risk of death (aOR: 1.00, 95% CI: 0.76–1.33) or death/HF (aOR: 1.06, 95% CI: 0.89–1.26) in patients exposed to KATP channel inhibitors versus patients not exposed to KATP channel inhibitors prior to their acute coronary syndrome. Conclusions Diabetes is associated with an increased risk of death or HF within 30 days of an acute coronary syndrome. However, we did not find any excess risk of death or HF associated with use of KATP channel inhibitors at the time of an acute coronary syndrome, raising doubts about the hypothesis that sulphonylureas inhibit the cardioprotective effects of myocardial KATP channels.